1107 Real-world deployment of point-of-care SARS-CoV-2 testing in the emergency department admission pathway can support the safe, accurate and rapid diagnosis of COVID-19. Issue 3 (21st February 2022) - Gunawardena, Ramith; Merrick, Blair; Gettings, Holly; Douthwaite, Sam; Nebbia, Gaia; Webber, Kay; Edgeworth, Jonathan; Batra, Rahul; Harrison, Hooi-Ling
Abstract : Aims/Objectives/Background: Patients admitted to hospital via the emergency department (ED) need to be separated by SARS-CoV-2 infection status to prevent transmission. Using clinical criteria alone is not feasible due to the range of symptoms and asymptomatic spread. Turnaround time of laboratory PCR assays (~6–24 hrs) hinders patient movement through the hospital with pressure on side-rooms pending results and exposure risk if unsuspected cases are moved into bays. Lateral flow devices (LFD) can provide a rapid diagnosis and aid patient movement. This implementation study aimed to assess the accuracy and safety of LFDs within an ED during a high-prevalence period. Methods/Design: Two rapid point-of-care tests (POCT) were introduced during December 2020: Cobas®-Liat® system (Roche Diagnostics) is a 20-minute assay comparable to laboratory PCR (in-house validation), and LFDs. Symptomatic patients with a positive LFD were cohorted on a 'red' ward. Asymptomatic patients with a negative result were allocated an 'amber' ward, pending lab PCR. Where there were discrepancies between results and symptoms; a Liat® was performed. The LFDs were validated by PCR swabs to determine true positive and false negative (FN) rates and to minimise fallout via contact tracing. The PCR cycle threshold (CT) values were recorded to evaluate the LFD sensitivity and specificity. Results were collected between December 2020-March 2021. Results/Conclusions: Comparing LFD with PCR results, the sensitivity and specificity were 70.7% and 99.1%. LFD FNs had higher CT values (≥25), indicating the beginning or end of infection – unlikely infectious. One period of false positives during lower prevalence revealed a faulty batch. During the study period 90% of patients left the ED with a virological diagnosis. We conclude that POCT can aid the diagnosis of COVID-19 in the ED when combined with existing laboratory-based PCR algorithms. We demonstrate a safe and effective use of POCT in the ED which could be replicated across other centres.